Meniere disease subtyping: the direction of diagnosis and treatment in the future. (1st February 2022) - Zhang, Sulin; Guo, Zhaoqi; Tian, E.; Liu, Dan; Wang, Jun; Kong, Weijia
ABSTRACT: Introduction: Meniere's disease (MD) is a chronic disorder of inner ear, characterized by audial and vestibular symptoms. It presents a great variability among patients in terms of clinical features, etiology, pathology, and response to the same therapy. It's challenging to diagnose and manage for its heterogeneity. Indeed, the consensus is reached that MD has subtypes. Identifying subtypes of MD is important for individualized therapy and further research. Areas covered: In this review, we examined the heterogeneity of MD. We also included the valid subtyping solutions and updated data regarding the association among subtypes, disease progression, and management. Expert opinion: MD is an etiologically multifactorial condition, and it might be a constellation of symptoms associated with endolymph hydrops, not a disease entity. So far, MD can be classified as distinct phenotypes and endotype, respectively based on symptoms, pathology, possible etiology, and co-existing condition. Patients in different subtypes present different clinical features and are suitable for different treatment. The identification of these subtypes will benefit both basic and clinical studies of MD, by helping achieve personalized therapy, accurate prognosis prediction and even disease screening in near future. Therefore, MD subtyping is the emerging direction of diagnosis and treatment in the future.